Summaries of papers presented at Irrigation Research Management Unit seminar series during 1994 - Haq, K.A.; Wijayaratna, C.M.; Samarasekera, B.M.S. (International Irrigation Management Institute, 1995)
The Irrigation Research Management Unit (IRMU) was established in mid-1992 in the Irrigation Department, Sri Lanka. The main objective of it is to identify research needs, conduct and coordinate research and disseminate research results to improve efficiency, productivity and profitability of irrigated agriculture. As part of its technology transfer program, the IRMU initiated a series of monthly seminars. During the year of 1994, eleven such seminars were held. The seminars covered the following program areas of IRMU and their distribution was as follows: Assessing and Improving Performance of Irrigation Systems-3, Local Management of Irrigation ofSystems-3, Operational Management of Water Delivery and Disposal-1, Crop Diversification-1, and Environmental Studies-3. Professionals and researchers from national and international agencies as well as free lance consultants dealing with irrigated agriculture and irrigation management participated as resource persons. Speakers came from the Department of Agriculture, the University of Peradeniya, the Irrigation Department, the Irrigation Research Management Unit, the Open University of Sri Lanka, the Field Crop Research and Development Institute-Maha Iluppallama, the International Irrigation Management Institute (IIMI) and the Food and Agriculture Organization of the United Nations/Regional Office for Asia and the Pacific (FAO/RAPA). IIMI was involved in three presentations (two on IRMU's work), the faculty members of the University of Peradeniya gave two presentations, the Irrigation Department, the Open University of Sri Lanka, the Field Crop Research and Development Institute, the Department of Agriculture, the FAO/RAPA and an independent consultant gave one presentation each. In addition to serving as a strong component of the technology transfer program, these seminars also provide essential inputs in strengthening IRMU's research program. These seminars, in general were well received, which was evident from the wide participation of different institutions and agencies. This publication contains summaries of the eleven seminars presented during the year 1994